Hubungan Dukungan Keluarga dengan Kepatuhan Pengobatan Hipertensi di Wilayah Kerja Puskesmas Tombulu - Najoan, Christania; Nurmansyah, Muhamad; Masi, Gresty (Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi, 2024)
Background: Uncontrolled hypertension can result in sudden death. Some of the causes are the lack of medication adherence to check-ups at health care facilities, and irregular consumption of anti-hypertensives. Objective: To determine the relationship between family support and adherence to hypertension treatment in the working area of the Tombulu Health Center. Method: This study used a cross-sectional study design. The population included 153 hypertensive patients. Results: This study showed that out of 155 respondents, most of them were in the category of high-level family support with medication adherence, 82 respondents (68.9%) used the Kolmogorov-Smirnov test showing a p-value of 0.023 α 0.05, which means that there is a relationship between family support and treatment adherence. Conclusion: There is a relationship between family support and medication adherence in respondents who experience hypertension at the Tombulu Health Center, that is, the average respondent has high family support and moderate medication adherence.